A NEW DIRECTION IN ARABIC MORPHOSYNTACTIC STUDIES: INTEGRATING CLASSICAL THEORY, MODERN LINGUISTICS, AND PEDAGOGICAL APPLICATIONS - Muhammad Fathin Haqqar; Hamzah (PT. Jurnal Center Indonesia Publisher, 2026)
Traditional Arabic linguistic studies often fall into a dichotomy that separates Nahwu (syntax) and Sharf (morphology), causing learners to lose the functional orientation of the language. This research aims to formulate a new direction in Arabic morphosyntactic studies through the integration of classical theory, modern linguistics, and pedagogical applications. Using a qualitative-descriptive approach with a library research method, data were analyzed comparatively and integratively from various reputable scientific literatures. The research results show that the integration of Al-Jurjani's Nazhm theory with systemic functional and generative-transformational linguistic perspectives is capable of providing a more logical explanation of Arabic language structures. Furthermore, digitalization through corpus analysis and computational linguistics enables empirical mapping of language patterns to support AI development. Pedagogically, the implementation of an integrative approach that unites the teaching of Nahwu and Sharf, alongside the utilization of data-based media, has proven to be more effective in enhancing students' communicative skills compared to conventional methods. This research concludes that strengthening morphosyntactic studies is a crucial step in modernizing Arabic language learning in the global era.